Characterisation of proteolysis profile of Argentinean sheep cheeses made by two different production methods - Candioti, Mario César (2010)
BACKGROUND: In this work the proteolysis profiles of Argentinean sheep cheeses made by two different production methods were studied in order to develop products with typical and defined features. Cheeses with a starter of Streptococcus thermophilus, curd cut to corn grain size, washed and heated to 43◦C (S cheeses) and cheeses with a mixed starter of Streptococcus thermophilus, Lactobacillus helveticus and Lactobacillus bulgaricus, curd cut to rice grain size, unwashed and heated to 47 ◦C (L cheeses) were manufactured. The cheeses were ripened at 12 ◦C and 80% relative humidity for 180 days and samples were taken throughout this period. RESULTS: Gross composition and primary proteolysis were similar for both types of cheeses. Streptococci counts diminished from 109 to 107 colony-forming units g−1 during ripening in both S and L cheeses. Lactobacilli counts in L cheeses decreased during ripening and disappeared at 180 days. L cheeses had significantly lower pH values and showed higher peptidolysis than S cheeses. Triangle sensory evaluation indicated important differences between the two types of cheeses. CONCLUSION: S cheeses had a low proteolysis level and a soft flavour, making them appropriate for consumption after a short ripening time. L cheeses had a higher proteolysis level and more intense sensory characteristics, making them appropriate for consumption after a longer ripening time.